Mechanistic Investigation on Anti-Nociceptive Potential of Bartogenic Acid Containing Barringtonia racemosa Fraction in Experimental Models of Pain (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Barringtonia racemosa (B. racemosa) is a tropical medicinal plant possessing interesting biological activities. B. racemosa fruits are traditionally used in India for the treatment of pain, inflammation, and rheumatic conditions. Earlier, we have reported anti-inflammatory activity of ethyl acetate fraction (BREAF) obtained from B. racemosa fruits in animal models of inflammation and delayed-type hypersensitivity. The present study aimed to assess the anti-nociceptive activity of BREAF. Acetic acid-induced writhing test, and hot plate and tail immersion tests were employed to study the effect of BREAF on peripheral and central pain mechanisms, respectively. The involvement of opioid system was confirmed through naloxone antagonism. Formalin induced pain test was performed to assess the effect of BREAF on neurogenic and inflammatory pain components. Capsaicin induced pain models were used to investigate the involvement of transient receptor potential vanilloid 1 receptor. The BREAF reduced writhing episodes and delayed the onset of acetic acid-induced writhings. The raised percentage maximum protective effects by BREAF in hot plate and tail immersion tests suggest the efficacy of BREAF in pain alleviation. A reversal of the analgesic effect of BREAF following naloxone treatment indicates the involvement of opioid receptors. The BREAF also inhibited inflammatory and neurogenic components of formalin-induced pain. The inhibition of capasaicin induced pain to some extent by the BREAF indicates the possibility of involvement of TRPV1 receptors. This study reinforces the traditional use of B. racemosa in the treatment of painful conditions. However, further studies are reasonable to explore the detailed mechanism(s) of the anti-nociceptive action of BREAF.